2019
DOI: 10.1021/acs.energyfuels.9b01584
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Clay Content and Type of Algerian Sandstone Rock Samples on Water–Oil Relative Permeabilities

Abstract: The objective of this work is to study the effect of certain factors on oil−water relative permeability curves following a considerable drop in the production of certain oil wells at the Hassi Messaoud field in southern Algeria. In the present study, oil−water relative permeability experiments and irreducible water (S wi ) and residual oil (S or ) saturations have been investigated. The effect of the clay particle content in the samples (such as illite and kaolinite) on oil recovery is investigated. Indeed, ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…The flow capacity of the tight sandstone gas reservoir is weak. By comparison, it can be found that, in the gas-water relative permeability curve of the clay-silt sediment, the irreducible water saturation is much higher than that of other reservoirs, which is determined by the high clay content of the clay-silt sediment [24]. It also directly determines that the mobile gas porosity in the clay-silt sediment is very low.…”
Section: Resultsmentioning
confidence: 96%
“…The flow capacity of the tight sandstone gas reservoir is weak. By comparison, it can be found that, in the gas-water relative permeability curve of the clay-silt sediment, the irreducible water saturation is much higher than that of other reservoirs, which is determined by the high clay content of the clay-silt sediment [24]. It also directly determines that the mobile gas porosity in the clay-silt sediment is very low.…”
Section: Resultsmentioning
confidence: 96%
“…However, the main factor is the change in wettability. In general, the greatest increase in oil recovery factor by LSWI occurs when the content of salts in the injection water is less than in the formation water (Al-Shalabi and Sepehrnoori 2016; Akkal et al 2019). During the LSWI process, the clay swelling phenomenon can be observed, after which the clay particles can dissolve in brine, then migrate, settle, and get stuck in the pores (Sameni et al 2015;Garcia-Olvera and Alvarado 2017).…”
Section: Introductionmentioning
confidence: 99%